Respuesta :

Step-by-step explanation: please see attached to PDF document.



Ver imagen jmidwest

Answer:

a) 6

b) 1/3

c) 2

Step-by-step explanation:

a) 3 ( x + 1 ) - x = 15. expand the bracket

3x + 3 - x = 15

2x + 3 = 15. collect the like terms

2x = 15 - 3.

2x = 12.

x = 12/2 = 6

b) 5 ( x + 2 ) - 2x = 11. expand the bracket

5x + 10 - 2x = 11

3x + 10 = 11. collect the like terms

3x = 11 - 10

3x = 1

x = 1/3

c) 6 ( 1 - 2x ) = - 4 - 7x. expand the bracket

6 - 12x = -4 -7x. collect the like terms

6 + 4 = -7x + 12x

10 = 5x

or

5x =. 10

x = 10/5 = 2

PLEASE MARK ME BRAINLIEST

ACCESS MORE